A schwannoma at the lower cerebellopontine angle mimicking a brainstem glioma on neuroimaging: case report - Zhang, Kui; Wenhu Li; Kai Zhao; Ninghui Zhao; Chongjing Zhang (Journal of the Pakistan Medical Association, 2026)
This study reports the case of a schwannoma in the inferior cerebellopontine angle (CPA) that mimicked a brainstem glioma in imaging. The patient was a 35-year-old male, who presented in February 2023 with dizziness that had persisted for six months and exacerbated on moving the neck. Imaging examinations, specifically cranial magnetic resonance imaging (MRI), revealed a mass in the left brainstem and cerebellar region, measuring approximately 3.7 × 2.6 × 3.8 cm. The mass was irregular in shape, showing slightly long T1 and mixed T2 signals. It locally compressed the fourth ventricle, and after contrast-enhanced scanning, significant heterogeneous enhancement was observed. Magnetic resonance spectroscopy (MRS) indicated that the peak heights of N-acetylaspartate (NAA) and choline complex in the lesion were approximately 0.049 and 0.524, respectively. Due to the extremely similar imaging features to those of a brainstem glioma, it was initially misdiagnosed as glioma. Total surgical resection was performed, and post-operative pathology confirmed it to be a schwannoma. The patient recovered well after the operation, the symptoms disappeared and no neurological deficits remained. This type of schwannoma is extremely rare and is highly likely to be misdiagnosed as a brainstem glioma due to its imaging manifestations. This case emphasises the importance of cautious diagnostic evaluation and surgical management of such rare tumours, providing valuable reference for clinical practice. Keywords: Schwannoma, Brainstem glioma, Neuroimaging, Persistent dizziness, Surgery, Tumour.